Geotechnical investigation of road pavement failure along arigidi / oke - agbe akoko, southwestern, Nigeria - Henry Tolulope Ogunribido, Thompson; Ezekiel Fadairo, Tunde (International Journal of Physical Research, 2020)
Twenty soil samples collected from the failed portions in the study area were air dried for two weeks before analyses. Each soil samples were subjected to eight engineering tests which include: natural moisture content, atterberg limit, specific gravity, compaction, unconfined compressive strength, California bearing ratio, grain size and hydrometer analysis. Results showed that the natural moisture content ranged from 17.7% to 37.8%, liquid limit from 48.5% to 62.4%, plastic limit from 18.3% to 26.8%, plasticity index from 25.7% to 37.7%, shrinkage limit from 5.8%-12.5%, optimum moisture content from 14.2% to 32.4%, maximum dry density from 1301 Kg/rn3 to 2002 Kg/rn3. Soaked California bearing ratio ranged from 5% to 17%, unsoaked from 15% to 38%, specific gravity from 2.5 to 2.68, unconfined compressive strength r from 112.8 Kpa to 259.7 Kpa, shear strength from 56.4 Kpa to 129.9 Kpa and hydrometer analysis from 48.5% to 72.1%. Based on the Federal Government specifications for pavement construction, for the soil to be suitable, stabilization with bitumen, Portland cement, lime, coal fly ash, and saw dust should be done. Road pavement failure along Arigidi â€“ Oke Agbe road was due to poor engineering geological condition of the sub-grade soils and poor drainage systems. Â Â